THE PROTECTION OF 2 - 10 YEARS OLD CHILDREN’s EGO BOUNDERS - Silina, O.V. (Modern Psychology, 2019)
Protection of boundaries of Self is a system of actions aimed at preserving physical and psychological well-being. In psychological science there is no consensus on the role of sibling status in the development of a child’s personality. We assume that the protection of the boundaries of Self in only, first-born and second-born children will be qualitatively different. The study was of a qualitative nature, the main methods were an included observation and simulation of situations. It has been shown that only and second-born children in the family have the most adaptive boundaries, with a well-built system of protection of their own psychological space with a focus on personal attitude to the social situation. Firstborns protect their boundaries, based on social norms or opinions of an adult.
Keywords: boundaries of self, protection of boundaries of self, sibling status, birth order.